Practical sports coaching (Routledge, Taylor & Francis Group, 2015)
"Practical Sports Coaching is a thorough and engaging guide for all sports coaching students and practitioners. Drawing on real-life case studies and examples, the book is designed to develop practical coaching skills and provides readers with the methods and tools they need to become an expert coach. Structured around all facets of the coaching process, the text comprehensively covers topics such as: preparation for coaching mentoring the philosophy of coaching direct intervention coaching methods the use of modern technology. The book's practical approach allows the reader to consider common challenges faced by coaches, suggesting solutions to performance concerns and preparing students for the realities of professional sports coaching. A companion website containing presentation slides and useful weblinks makes the book a complete resource for students and lecturers alike. Practical Sports Coaching helps to bridge the gap between theory and practical coaching skills, and is an essential text for coaching students looking to deepen their understanding of sports coaching and experienced coaches developing their own practical skills"--